COVID-19 crisis: Lessons learned for future policy research - Jean-Sébastien Fontaine; Corey Garriott; Jesse Johal; Jessica Lee; Andreas Uthemann (Bank of Canada, 2021)
Fixed-income markets were disrupted at the beginning of the COVID-19 crisis. As whole industries temporarily shut down, businesses and households ran down their savings or needed credit to survive income losses. As volatility increased, portfolio managers sold securities to manage their leveragedexposures or meet actual and anticipated margin calls and redemption requests. In financial markets, a substantial part of the demand for money came from asset managers. When the dealer arms ofcommercial banks approached their internal risk limits, the demand for money outpaced their willingness to deal or lend against securities, and trading costs rose in core and peripheral funding markets. The unprecedented scale of interventions by the Bank of Canada and other central banks raises questions that we pose for future policy research. Can central banks' policies and crisis interventions in financial markets better reflect the growing role that asset managers play in the financial system? And can the structure of financial markets be made less reliant on the capacity of banks to supply money?
Keywords: D47; E41; E5; G01; G14; G20; G21; G23; 330; Coronavirus disease (COVID-19); Financial markets; Financial System